Guidance and Counseling Management Strategy in Schools in Creating Discipline - Anisa Afriani; Neviyarni S; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Guidance and counseling management is an activity that begins with planning guidance and counseling activities, organizing activities and all supporting elements of guidance and counseling, mobilizing human resources to carry out guidance and counseling activities, motivating human resources so that guidance and counseling activities achieve goals and evaluating guidance and counseling activities to find out whether all service activities have been implemented and to find out the results. The method used in writing this article is a literal study which is a written summary quoted from journals, articles, books and other documents, which contain descriptions of past or current information that is relevant to the title of the study. The results of this study are that the guidance and counseling management strategy in schools in creating discipline in students needs to be carried out by BK teachers/counselors accompanied by cooperation between related parties in the school. All parties have an obligation to support every program that exists in an effort to develop students' self-development.